Measuring "Village Regulations" in Urban Community Relations in the City of Bukittinggi, West Sumatra - Helfi Helfi; Fajrul Wadi; Beni Firdaus; Dahyul Daipon (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
Migrant workers usually come to a city for economic reason as cities are still deemed to provide much available economic opportunities. Urban communities, on the other hand, typically preserve village regulation that they specifically formulate in dealing with comers like what occurs in Bukittinggi, West Sumatra. On the basis of it, this article aims to portray the village regulation taking sample at the Campago Guguak Bulek Nagari, Mandiangin Koto Selayan, Bukittinggi, West Sumatra. The research problems are on the current village regulation from its establishment, form, dissemination, sanction, stratification of legal subjects, and the effect as well as how the regulation will look like in the future. This is a qualitative normative research using in-depth interview with comers who directly deal with local regulations as well as local communities as the one who preserve the regulation. It found that regulations at Bukittinggi emphasize protection of the local economy and socio-cultural aspect. More specifically, it aims to regulate life together, protect rights and obligations as well as social institutions, maintain safety and order, and improve community welfare. This all make the village regulation deserve for future preservation. (Salah satu alasan perantau mendatangi sebuah kota biasanya adalah faktor ekonomi. Kota-kota besar hingga hari ini masih dianggap menawarkan banyak peluang ekonomi. Masyarakat kota, di sisi lain, biasanya memiliki berbagai aturan khusus bagi para pendatang seperti yang terjadi di Bukittinggi, Sumatera Barat. Dari situ, artikel ini ingin memotret hubungan antara aturan lokal di Bukittinggi dengan para pendatang di situ, khususnya di Kelurahan Campago Guguak Bulek, Mandiangin Koto Selayan, Bukittinggi, Sumatra Barat. Pertanyaan penelitian ini adalah seputar peraturan kampung yang berlaku mulai dari pembentukan, bentuk-bentuk, sosialisasi, sanksi, subyek hukum, dan efeknya. Selain itu, akan dilihat juga bagaimana prediksi akan ‘nasib’ peraturan ini di masa mendatang. Penelitian ini bersifat normatif-kualitatif dengan wawancara mendalam kepada para pendatang maupun komunitas lokal sebagai salah satu metode penggalian data utamanya. Hasilnya menunjukkan bahwa aturan-aturan tersebut menitikberatkan pada perlindungan sosial—ekonomi lokal, utamanya perihal aturan-aturan hidup berdampingan, perlindungan hak dan kewajiban, pranata sosial, jaminan keamanan dan ketentraman, serta peningkatan kesejahteraan. Inilah yang membuat peraturan tersebut layak untuk tetap berlaku hingga di masa mendatang)